Fitoremediasi Kadar Logam Berat Kromium (Cr) pada Limbah Batik Menggunakan Eceng Gondok dan Kangkung Air - Amnan Haris; Ade Murti Muzaiyanah; Andin Vita Amalia; Sri Ngabekti; Andhina Putri Heriyanti (Universitas PGRI Palembang, 2025)
The home-scale batik industry in Pekalongan, while contributing to the local economy, generates wastewater containing heavy metal chromium (Cr) and organic pollutants, posing environmental risks. This study evaluated the effectiveness of phytoremediation using Eceng gondok (Eichhornia crassipes), kangkong air (Ipomoea aquatica), and their combination to reduce Cr, BOD, COD, and TSS in batik wastewater. Experiments were conducted at three wastewater concentrations (25%, 50%, 100%) over 14 days. Results showed significant reductions in all parameters: Cr removal was highest with WS at 100% concentration (93.9%), BOD and COD decreased up to 90%, and TSS decreased up to 91.1% with the WH-WS combination. pH (6.9–7.3) and temperature (27–32.8°C) remained optimal. These findings indicate that WH, WS, and their combination provide an effective and eco-friendly approach for treating batik wastewater in Pekalongan.